Hyper Elliptic Curve Cryptography (HECC) to Ensure Data Security in the Cloud - Nagendran, N.; Thillaiarasu, N.; Chandrika, P.; Chethana, R. (International Journal of Engineering and Technology, 2018)
In todayâ€™s technological world, cloud computing is emerging as a trendsetting information technology service for storing data and resources and retrieving them from the Internet rather than direct server connection. This technology also enables users to save them in a remote database. But the main concern with this technology is about the security of data stored in the cloud. Since users rely on third party services for data storage, they are highly vulnerable to attacks and data exploitation. Cloud services offer a multitude of security tools to safeguard user data but they face some disadvantages like data leakage, denial of service, eavesdropping, lack of safety standards etc., This paper proposes a efficient method for safeguarding cloud data through Hyper elliptic curve cryptography (HECC). The proposed cryptographic technique offers effective encryption and decryption of data in the cloud.Â